Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To solve the expression [tex]\(\sqrt{-108} - \sqrt{-3}\)[/tex], let's break it down step by step.
1. Simplify [tex]\(\sqrt{-108}\)[/tex]:
- We know that [tex]\(\sqrt{-1} = i\)[/tex], where [tex]\(i\)[/tex] is the imaginary unit.
- Thus, [tex]\(\sqrt{-108}\)[/tex] can be expressed as [tex]\(\sqrt{108} \cdot i\)[/tex].
Next, we simplify [tex]\(\sqrt{108}\)[/tex]:
[tex]\[ \sqrt{108} = \sqrt{36 \times 3} = \sqrt{36} \cdot \sqrt{3} = 6\sqrt{3} \][/tex]
Therefore,
[tex]\[ \sqrt{-108} = 6\sqrt{3} \cdot i = 6\sqrt{3}i \][/tex]
2. Simplify [tex]\(\sqrt{-3}\)[/tex]:
- Similarly, we express [tex]\(\sqrt{-3}\)[/tex] as [tex]\(\sqrt{3} \cdot i\)[/tex].
[tex]\[ \sqrt{-3} = \sqrt{3} \cdot i = \sqrt{3}i \][/tex]
3. Subtract the simplified expressions:
[tex]\[ \sqrt{-108} - \sqrt{-3} = 6\sqrt{3}i - \sqrt{3}i \][/tex]
4. Combine like terms:
Factor out the common term [tex]\(\sqrt{3}i\)[/tex]:
[tex]\[ 6\sqrt{3}i - \sqrt{3}i = (6 - 1)\sqrt{3}i = 5\sqrt{3}i \][/tex]
Hence, the expression equivalent to [tex]\(\sqrt{-108} - \sqrt{-3}\)[/tex] is:
[tex]\[ 5 i \sqrt{3} \][/tex]
So, the correct answer is:
[tex]\[ \boxed{5i \sqrt{3}} \][/tex]
1. Simplify [tex]\(\sqrt{-108}\)[/tex]:
- We know that [tex]\(\sqrt{-1} = i\)[/tex], where [tex]\(i\)[/tex] is the imaginary unit.
- Thus, [tex]\(\sqrt{-108}\)[/tex] can be expressed as [tex]\(\sqrt{108} \cdot i\)[/tex].
Next, we simplify [tex]\(\sqrt{108}\)[/tex]:
[tex]\[ \sqrt{108} = \sqrt{36 \times 3} = \sqrt{36} \cdot \sqrt{3} = 6\sqrt{3} \][/tex]
Therefore,
[tex]\[ \sqrt{-108} = 6\sqrt{3} \cdot i = 6\sqrt{3}i \][/tex]
2. Simplify [tex]\(\sqrt{-3}\)[/tex]:
- Similarly, we express [tex]\(\sqrt{-3}\)[/tex] as [tex]\(\sqrt{3} \cdot i\)[/tex].
[tex]\[ \sqrt{-3} = \sqrt{3} \cdot i = \sqrt{3}i \][/tex]
3. Subtract the simplified expressions:
[tex]\[ \sqrt{-108} - \sqrt{-3} = 6\sqrt{3}i - \sqrt{3}i \][/tex]
4. Combine like terms:
Factor out the common term [tex]\(\sqrt{3}i\)[/tex]:
[tex]\[ 6\sqrt{3}i - \sqrt{3}i = (6 - 1)\sqrt{3}i = 5\sqrt{3}i \][/tex]
Hence, the expression equivalent to [tex]\(\sqrt{-108} - \sqrt{-3}\)[/tex] is:
[tex]\[ 5 i \sqrt{3} \][/tex]
So, the correct answer is:
[tex]\[ \boxed{5i \sqrt{3}} \][/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.